Enhancing the Dynamic Stability of Pylons via Their Drag and Lift Coefficients by Finite Volume Method - Van My Nguyen; Van Than Chau (Buildings, 2023)
This study aimed to estimate the drag and lift coefficients of the long-span bridge pylon using the finite volume method (FVM). The k-ω turbulence model was applied to analyze the behavior of wind flow around the pylon, yielding drag and lift coefficient values with an error of 0.98% compared to a previous tunnel experiment. Four recommended cross-sections were proposed to reduce drag and lift forces acting on the pylon, including concave, convex, crossing, and chamfering cross-sections. The finding indicated that drag and lift coefficient decreased for all cross-sections. Cutting edges of concave, convex, and chamfering cross-sections with a ratio ranging from 0.2 to 0.3 has the greatest impact on reducing drag coefficient, while the crossing cross-section with a cutting ratio ranging from 0.2 to 0.25 has the lowest drag coefficient. The maximum reduction in drag and lift coefficients were 23.69% and 13.14% for concave and chamfering cross-sections. Thus, cutting edges of cross-sections is an effective method to enhance the aerodynamic stability of the pylon. Additionally, we evaluated drag and lift coefficients for different wind direction angles. The angles of 0, 30, and 90 degrees resulted in the highest drag coefficient, while the angle of 0 degrees and the angle of 90 degrees resulted in the lowest and highest lift coefficient, respectively. This study not only provides recommendations for cross-sections that reduce forces acting on the pylon but also provides the intensity of this reduction through corresponding estimation equations. In conclusion, concave and chamfering cross-sections are the most effective in reducing drag and lift coefficients, or, in other words, increasing the aerodynamic stability of the pylon.